Management of Infantile Spasms: An Updated Review - Iype, Mary; Koshy, Kiren George (International Journal of Epilepsy, 2020)
Infantile spasms remain the most challenging of the epileptic encephalopathies of childhood. Infantile spasms are classified as an epileptic encephalopathy, as the adverse cognitive and behavioral burden of the condition is out of proportion to the burden one would expect from the underlying etiology or the accompanying magnetic resonance imaging. The ictal and interictal electroencephalographic (EEG) activity is presumed to contribute to the progressive cerebral dysfunction. In many of these children, the underlying etiology also contributes to the severe mental subnormality and autistic behavior. Though it is the syndromic approach that guides the pediatric epileptologist, it is best to keep in mind that one syndrome may evolve into another in infancy and early childhood. A baby with Ohtahara syndrome may, after 2 to 7 months, begin to have spasms. Lennox-Gastaut syndrome with its typical seizure types and EEG may evolve in a child with infantile spasms.The unique modalities used in the treatment of infantile spasms make early recognition important. It is, however, also of paramount importance to make an etiological diagnosis as the underlying etiology may be eminently treatable. The treating physician cannot abandon them as wholly “intractable” epilepsy. The excellent response to treatment in the few who just cannot be defined or accurately predicted drives the physician to exercise his brain. Use of the two well-accepted modalities of treatment; vigabatrin and adrenocorticotrophic hormone singly or in combination, oral steroids in high dose, ketogenic diet, the conventional antiepileptic medications, and strategies to target the basic cause have been tried out by various clinicians. Here, we have made an attempt to collate evidence and describe the progress in the management of infantile spasms.
Keywords: infantile spasms; adrenocorticotrophic hormone; vigabatrin